Financial Strain and Health Status Among European Workers: Gender and Welfare State Inequalities - Lucía Artazcoz; Lucía Artazcoz; Lucía Artazcoz; Lucía Artazcoz; Imma Cortès-Franch; Imma Cortès-Franch; Imma Cortès-Franch; Imma Cortès-Franch; Vicenta Escribà-Agüir; Fernando G. Benavides; Fernando G. Benavides (Frontiers Media S.A., 2021)
Objectives: Although in-work poverty has been increasing, in Europe policy about poverty and social exclusion tends to focus on labor market participation, independently of the level of remuneration and the quality of work, and studies about financial strain among workers, as well as on its relationship with health status, are still scarce. The objectives of this study were: (1) to compare the prevalence of financial strain among workers among different welfare state typologies, and (2) to examine whether the relationship between financial strain and health status differs by welfare state regime. For both objectives we examined whether there were gender differences.Methods: We conducted a cross-sectional study using data from the 6th European Working Conditions Survey of 2015 and selected a subsample of all employees from the EU28 aged 16-64 years (13,156 men and 13,225 women).Results: There were large differences in the prevalence of financial strain between welfare state typologies, which were not explained by individual factors. Additionally, differences across welfare regimes were greater among women. Nordic countries had the lowest prevalence (12.1% among men and 12.3% among women) whereas Southern European countries had the highest (49.5% among men and 47.9% among women). In both sexes and in all welfare state typologies, financial strain was associated with poor self-perceived health status and poor psychological well-being. Whereas, Southern European countries had the highest prevalence of financial strain, the magnitude of the association with health status was smaller than in other country typologies.Conclusion: In Europe, policies are needed to address the specific structural factors leading to financial strain as well as its relationship with health status among workers.